Treatment Approaches Towards the Management of Peptic Ulcer Disease in a Resource Constrained Setting - Nyirenda, Christopher; Mwelwa, Danny; Maliko, Catherine; Chimese, Mwinsa; Chinkoyo, Sebastian; Zulu, Mabvuto; Maksoud, Gamal (British Journal of Healthcare and Medical Research, 2023)
Objective: To examine the treatment options advised towards the management of peptic ulcer disease (PUD) based on the available diagnostics in a resource limited setting. Design and Methods: A retrospective cross sectional study in which medical records for outpatients and inpatients attended to in the Department of Internal Medicine at a tertiary hospital in Ndola district between January 2019 and December 2019 were examined. The target population were adult male and female patients presenting for care and on whom a presumptive or definitive diagnosis of PUD was made within the period under review. The sample size estimate was determined using the Cochrane formula and a non-probability purposive sampling technique was used. The data collected was analyzed using Statistical Package for the Social Sciences (SPSS) software version 16.0 for Windows (SPSS Inc., Chicago, IL) and was double-checked for accuracy. Descriptive aspects of analyses were done through calculating frequencies, and percentages. Univariate analysis was carried out to determine the proportion of patients in each diagnostic approach. Results: A total of 388 peptic ulcer disease patients diagnosed and treated at Ndola Teaching Hospital were involved in the study. Among the 388 patients, 128 (33%) were females and 260 (67%) were males. The management of PUD was mostly medical, with 8.25% of the patients receiving antibiotics only, 14.43% of the patients receiving an antacid only which was omeprazole while 74.23% of the patients received triple therapy which comprises two antibiotics and an antacid. Of this proportion, none of them had a backup H. Pylori test done. The remaining 3.09% of the patients were not given any medication but only information, education and counselling. No other treatment modalities or surgical management were recorded. Study findings further showed that definitive diagnosis meant clear indication for triple therapy while presumptive diagnoses of peptic ulcer disease had varied management. The association between type of diagnosis and treatment was signified by a p value of 0.002. Conclusion: Most of the patients managed for peptic ulcer disease at NTH received presumptive therapy, a trend likely driven by lack of resources towards definitive diagnosis and justifying the need for more accurate diagnostic approaches.